The Integrated Prevention Model for Marijuana Smuggling in Land Border Region of Indonesia-Papua Nugini (Case: Muara Tami District, Jayapura City, Papua Province) - Maya, Heni Batara; Dermawan, Mohammad Kemal; Susanti, Vinitia (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis paper describes the need for an effective preventive model in preventing the smuggling of marijuana in the Indonesia-Papua New Guinea land border area in Muara Tami District, Jayapura Papua. The model applied so far is an outward-looking model where this model implements an integrated cross-border inspection, supervision, and security. The unstructured interview approach and the Delphi method were used in this study so that accurate data was obtained that in practice, the current model used still did not look professional and integrated, namely between cross-border service officers, Police and defense, Ondoaffi. Traditional leaders, religious leaders, and border communities in the Indonesia-Papua New Guinea region. Besides, the integration between Ministries/Institutions related to programs and budgets to prevent marijuana smuggling in the Indonesia-Papua New Guinea border area in Muara Tami District, Jayapura City, Papua Province is also still weak. The reason people who choose to smuggle marijuana is because they do not feel guilty and think that it is a profitable job with a strong social network, the behavior that neutralizes themselves that carrying marijuana is not a crime. Besides, the existence of problems such as geographic, demographic, and disturbance from armed crime groups (OPM) that have not received serious action are also factors related to the above problems. Based on this background, this dissertation provides a strategic step, contained several policy recommendations that can strengthen this model so that it is expected to be maximized and more efficient than the previous model.Keywords: Land Border Territory, Organized Crime, Social Networking, Neutralization, and the Delphi Method, The Crime Prevention Model of Cannabis Smuggling AbstrakTulisan ini menjelaskan tentang perlunya suatu model pencegahan yang berdaya guna dalam mencegah penyelundupan ganja di wilayah perbatasan darat Indonesia-Papua Nugini di Distrik Muara Tami, Jayapura Papua. Model yang diterapkan selama ini, yaitu model outward looking, yang menerapkan pemeriksaan, pengawasan dan keamanan lintas batas secara terpadu. Pada kenyataannya, penyalahgunaan ganja yang berasal dari Papua Nugini masih mengkhawatirkan di wilayah perbatasan. Dengan pendekatan wawancara tidak terstruktur dan metode Delphi diperoleh data akurat bahwa model yang dilakukan sekarang dalam pelaksanaannya masih belum terlihat professional dan terpadu antara petugas pelayanan lintas batas, petugas keamanan (Polisi) dan pertahanan (TNI), Ondoaffi (tokoh adat), tokoh agama dan masyarakat perbatasan di wilayah Indonesia-Papua Nugini. Selanjutnya, masih lemahnya keterpaduan antara Kementerian/Lembaga terkait program dan anggaran dalam rangka pencegahan penyelundupan ganja di wilayah perbatasan Indonesia-Papua Nugini di Distrik Muara Tami, Kota Jayapura Provinsi Papua. Masih adanya orang-orang memilih melakukan penyelundupan ganja karena tidak merasa bersalah dan merupakan pekerjaan yang menguntungkan, jaringan sosial yang kuat, terdapatnya perilaku yang menetralkan dirinya bahwa membawa ganja bukan suatu kejahatan. Serta persoalan yang masih belum serius diantisipasi seperti persoalan geografis, demografis dan gangguan dari kelompok kejahatan bersenjata (OPM). Terkait persoalan tersebut, disertasi ini akan memberikan suatu langkah strategis, dengan beberapa rekomendasi kebijakan yang menguatkan model ini bisa memaksimalkan dan berdaya guna dari model sebelumnya.Kata Kunci: Wilayah Perbatasan Darat, Kejahatan Terorganisir, Jaringan sosial, Netralisasi dan Metode Delphi, Model Pencegahan Kejahatan Penyelundupan Ganja АннотацияВ этой статье описывается потребность в эффективной превентивной модели предотвращения контрабанды марихуаны в сухопутной приграничной территории Индонезии-Папуа-Новой Гвинеи в районе Муара Тами, Джаяпура, Папуа. Применяемая до сих пор модель - это модель внешнего наблюдения, которая реализует интегрированный трансграничный контроль, надзор и безопасность. . Фактически злоупотребление марихуаной из Папуа-Новой Гвинеи по-прежнему вызывает беспокойство в приграничных территориях. С помощью подхода неструктурированного интервью и метода Дельфи получены точные данные о том, что текущая модель в ее реализации все еще не выглядит профессиональной и интегрированной между офицерами трансграничной службы, офицерами безопасности (полиция) и обороны (TNI), Ондоафи (традиционные лидеры), религиозными лидерами и приграничной общиной в территории Индонезия-Папуа-Новая Гвинея. Кроме того, все еще существует слабая интеграция между министерствами/ведомствами, имеющими отношение к программам и бюджетам, с целью предотвращения контрабанды марихуаны в приграничной территории Индонезии-Папуа-Новой Гвинеи в районе Муара Тами города Джаяпура, провинция Папуа. Некоторые люди по-прежнему предпочитают провозить марихуану контрабандой, потому что они не чувствуют себя виноватыми, и это прибыльная работа с сильной социальной организацией; они считают, что ношение марихуаны не является преступлением. Такие проблемы, как географические, демографические и вмешательство вооруженных преступных группировок (OPM), которые еще ждут своего решения, также являются факторами, способствующими этому преступлению. Основываясь на этом, данная статья даёт стратегический шаг с несколькими рекомендациями по политике, которые смогут максимально укрепить эту модель и сделать её более эффективной по сравнению с предыдущей моделью.Ключевые Слова: Сухопутная Приграничная Территория, Организованная Преступность, Социальные Сети, Нейтрализация И Метод Дельфи, Модель Предупреждения Контрабанды Марихуаны.